Leadership at Local Level: Approach to an Impact on the Democratization Processes in Latvia - Abolina, Inese (Socialiniai tyrimai, 2016)
The leader’s role is decisive when developing a strategic vision and strengthening democracy at local aswell as at highest level. Local government leaders should develop new approaches to further development, be able to adapt to the time of frequent change and thus enhance the effectiveness of organizations and leadership at local level.The aim of the paper is to examine the development of leaders’ skills and competences. Most often leadership skills are being developed at school, within NGOs and society. It is important to be organized and have good communication skills, be able to generate and disseminate ideas.Leaders’ characteristics, leadership skills and their development, future challenges are discussed in the first part of this paper.In the second part, the impact of local government leaders on democracy strengthening at local level areanalysed.This research shows that the activity of local government leaders has a huge impact on democratization processes in Latvia therefore motivation for further development, lifelong learning and competence development play a very important role.
Keywords: leader; political leadership; democracy